Assembly of a Hybrid Formica aquilonia × F. polyctena Ant Genome From a Haploid Male. (8th April 2022) - Nouhaud, Pierre; Beresford, Jack; Kulmuni, Jonna
Abstract: Formica red wood ants are a keystone species of boreal forest ecosystems and an emerging model system in the study of speciation and hybridization. Here, we performed a standard DNA extraction from a single, field-collected Formica aquilonia × Formica polyctena haploid male and assembled its genome using 60× of PacBio long reads. After polishing and contaminant removal, the final assembly was 272 Mb (4687 contigs, N50 = 1.16 Mb). Our reference genome contains 98.5% of the core Hymenopteran BUSCOs and was pseudo-scaffolded using the assembly of a related species, F. selysi (28 scaffolds, N50 = 8.49 Mb). Around one-third of the genome consists of repeats, and 17 426 gene models were annotated using both protein and RNAseq data (97.4% BUSCO completeness). This resource is of comparable quality to the few other single individual insect genomes assembled to date and paves the way to genomic studies of admixture in natural populations and comparative genomic approaches in Formica wood ants.